Analysis of Student Learning Difficulties in Class XI Matrix Material at SMA Negeri 2 Kisaran - Wanahari, Maulidia; Dewi, Sri Rahmah; Gunarto, Bayu (Holistic Science, 2024)
This research aims to analyze learning difficulties in the matrix material of class XI Mipa students at SMA Negeri 2 Kisaran. This type of research is descriptive research with a qualitative approach to describe and describe phenomena by paying attention to characteristics, quality and relationships between activities. Data collection was carried out by A. students being asked to complete a description test about the matrix consisting of 4 questions on the answer sheet that had been prepared; (2) take several answers from students who have difficulty for analysis. Data analysis was carried out through stages identifying and classifying student errors. The subjects of this research were 36 students of class XI MIPA 2 SMA Negeri 2 Kisaran. The research instrument used was a description test of the matrix material. Of the 4 questions that had to be solved, the percentage of students who answered the questions correctly was 47%, 36%, 42% and 33%, respectively. The results of the analysis show that students experience difficulties in solving matrix questions, including: A. difficulties in using concepts, B. difficulties in using principles, C. difficulties in solving problems